Gastric Cancer Stem Cells: A Glimpse on Metabolic Reprogramming - Addeo, Martina; Di Paola, Giuseppina; Verma, Henu Kumar; Laurino, Simona; Russi, Sabino; Zoppoli, Pietro; Falco, Geppino; Mazzone, Pellegrino (Frontiers in Oncology, 2021)
Gastric cancer (GC) is one of the most diffuse cancer-related death worldwide. Recently, an increased number of evidences have implied that gastric cancer stem cells (GCSCs) play an important role in the initiation and progression of GC. This subpopulation comprises cells with several features, such as self-renewal capability, high proliferating rate, and ability to modify their metabolic program, that allow them to resist to current anticancer therapies. Metabolic pathway intermediates play a pivotal role in regulating cell differentiation both in tumorigenesis and during normal development. Thus, the dysregulation of both anabolic and catabolic pathways constitutes a significant opportunity to target GCSCs in order to eradicate the tumor progression. In this review, we discussed the current knowledges about metabolic phenotype that supports GCSC proliferation and we overviewed the drugs that selectively target metabolic intermediates.